2009
DOI: 10.1177/1548051809331503
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and Leadership

Abstract: Learning to lead online is imperative for the future of leadership. Whether they like it or not, even if they prefer face-to-face interactions, leaders of the future must be able to develop a sense of closeness with others, whether they be down the hall or around the world. In this study, face-to-face residential workshops were matched with online sessions over an 18-month period. Data from 75 participants, ranging from 18-year-olds to senior corporate executives, suggest that levels of online communication ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Similarly, out of 11 non-randomised quantitative studies only three [86,89,120] met all the criteria assigned to this category. While one of these studies [6] failed to meet any criteria, the remaining eight studies showed limited level of representativeness in the sample [61,78], incomplete reporting of data [30] and the insufficient account of confounders in design and analysis [100].…”
Section: Rq3: To What Extent Did Such Research Meet the Established Q...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, out of 11 non-randomised quantitative studies only three [86,89,120] met all the criteria assigned to this category. While one of these studies [6] failed to meet any criteria, the remaining eight studies showed limited level of representativeness in the sample [61,78], incomplete reporting of data [30] and the insufficient account of confounders in design and analysis [100].…”
Section: Rq3: To What Extent Did Such Research Meet the Established Q...mentioning
confidence: 99%
“…However, there are a four studies [36,78,100,112] that lean towards a more critical perspective, making passing observations of greater complexity of leadership processes. The location of leadership in most studies was presented as uncontested, with little reflection on the inter-dependencies between stakeholders, or possible tensions between different organizational levels.…”
Section: Studies In Teaching and Learning) B) Digital Organisational ...mentioning
confidence: 99%
“…E-Leadership is defined as a social influence process mediated by AIT (Advanced Information Technology) to produce a change in attitudes, feelings, thinking, behavior, and/or performance of individuals, groups, and/or organizations. Kolb et al (2009) in their study of 75 individuals ranging from 18-year olds to senior corporate executives have found that technical connectivity is directly related to leadership effectiveness. Huang et al (2010) found through a laboratory study that transactional leadership behaviors improve task cohesion of the team, whereas transformational leadership behaviors improve cooperative climate within the team which, in turn, improves task cohesion, in virtual world subject to perceived media richness.…”
Section: Personal Motivation and Social Media Usementioning
confidence: 99%
“…The possibility of multi-media, many to many interactions through advanced information technology (AIT) collectively known as Web 2.0 has moved more work online; leadership practice is now enacted more frequently in virtual team settings (Hambley, 2007;Lipnack & Stamps, 1999;Ziek & Smulowitz, 2014). Hence the context for leadership as 'a social influence process' (Parry, 1998) increasingly depends on the quality and availability of electronic channels between highly interconnected network nodes who may be individuals or groups (Kolb, Prussia, & Francoeur, 2009). Avolio et al (2000) dubbed this intersection of technological infrastructure and distributed leadership influence 'e-leadership'.…”
Section: Introductionmentioning
confidence: 99%